Susceptibility of Aeromonas salmonicida subsp. salmonicida bacteria from French farmed trout to antibiotics commonly used in fish farming, and attempt to set epidemiological cut-off values - Rostang, Antoine; Bachelet, Florine; Fournel, Catherine; Carabin, Titouan; Navarro-Gonzalez, Nora; Calvez, Ségolène (Frontiers in Microbiology, 2025)
Aeromonas salmonicida subsp. salmonicida (ASS) is a bacterium that can cause opportunistic infections in humans and animals. In farmed rainbow trout it causes furunculosis, with more frequent outbreaks when water temperatures are higher, an additional consequence of global warming. When infections occur, antibiotics are sometimes required. However, data on ASS susceptibility is limited. The aim of this study was to determine the distribution of Minimum Inhibitory Concentrations (MICs) of eight antibiotics commonly used in fish veterinary medicine in a population of pathogenic ASS, and to calculate provisional epidemiological cut-off values (called COEpid). To date, only four epidemiological cut-off values (ECV) have been established by CLSI, and none by EUCAST. In this study, 406 bacterial strains of ASS were collected exclusively from diseased French farmed trout over a 10-year period (2012–2021). A combination of PCR, MALDI-TOF and specific characteristics of the bacterial culture was used to identify each isolate to species level. All MIC data were obtained by the broth dilution method according to CLSI recommendations. Our COEpid meets the CLSI defined ECV for florfenicol (4 mg/L) and oxytetracycline (1 mg/L). In the absence of a defined ECV, we proposed a COEpid of 1 mg/L for doxycycline. For sulfadiazine alone, all strains tested were non-wild-type (NWT) with very high MICs. The COEpid was calculated as 4.8/0.25 mg/L for sulfadiazine + trimethoprim (one two-fold dilution difference from the ECV established by CLSI for ormetoprim + sulfadimethoxine). For quinolones, COEpid were 4 mg/L, 4 mg/L and 0.5 mg/L for oxolinic acid, flumequine and enrofloxacin, respectively, with a cross-resistance mechanism. This COEpid for oxolinic acid far exceeds the CLSI defined ECV (0.125 mg/L). A total of 12 strains (3%) were classified as NWT for all antibiotics tested. Over the period studied, the proportion of bacteria susceptible to the different molecules remained stable, except for the tetracycline family. These data will be available to establish internationally agreed epidemiological cut-off values, which are lacking for some antibiotics. These cut-offs are essential to assess and monitor the emergence of bacterial populations with resistance traits, and to establish clinical breakpoints for better use of antimicrobials in fish.